Be your own coach : your pathway to possibility - Braham, Barbara (Crisp Pub. Menlo ParkUS, 2000)
Identifies receiving promotion; achieving success; desiring growth; and experiencing failure as self-coaching openings, and outlines suitable coaching approaches for each situation. Provides opportunities for reader self-examination/self-awareness by presenting a variety of perspectives from which coaching opportunities may be viewed e.g. feelings, moods, intentions, beliefs, self-talk, actions. Explains the 4-stage coaching process i.e. letting go of 'baggage'; living with as yet unanswered questions; exploring new beginnings; and reflecting on progress. Explores 7 coaching tools for achieving breakthroughs including: choice management, self-inquiry, and commitment.